The Aesthetics of TikTok Content in Enhancing Tourists’ Intention to Visit Labuan Bajo - Salsabila, Nadhifa; Setiawan, Budi (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The phenomenon of TikTok content aesthetics has emerged as a new strategy in tourism promotion, including in Labuan Bajo. However, not all content produced has appealing aesthetic quality. Many videos still appear monotonous, lack creativity, or fail to highlight local uniqueness. As a result, some content falls short in building a strong destination image and instead gets lost in the increasingly saturated digital content competition. This research aims to examine in depth how the aesthetics of TikTok content contribute to increasing tourist interest in visiting Labuan Bajo, one of Indonesia’s super-priority destinations. Labuan Bajo was chosen as a case study not only because of its world-class tourism appeal but also because it is currently being actively promoted through digital branding strategies. The study employs a qualitative approach with a case study design. Data were collected through TikTok content observation, in-depth interviews with content creators and local tourism stakeholders, as well as literature analysis on smart tourism and destination branding. This approach was selected to uncover the underlying meaning behind aesthetic content strategies while also highlighting the challenges faced in their implementation. The findings reveal that the aesthetics of TikTok content play a significant role in building a positive image of Labuan Bajo, enhancing its visual appeal, and creating emotional connections between prospective tourists and the destination. Nevertheless, the research also identifies challenges such as limited digital literacy, uneven content quality, and the risk of narrative homogenization that may reduce local uniqueness. Based on these findings, the study recommends the development of destination branding strategies that are more adaptive to social media trends, including the creation of aesthetic guidelines rooted in local culture, digital literacy training for tourism stakeholders, and close collaboration between government, industry, and content creators. Through these efforts, Labuan Bajo has the potential to strengthen its position as a leading world-class destination.